ANALISIS PELAKSANAAN KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN BIOLOGI DI SMA SE-KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - -, Wulandari; Lestari, Rena; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This aims study to investigate the implementation of pedagogical competence of teachers in the teaching ofbiology in high schools in District of Tambusai Utara. This research instrument using a questionnaire andanalyzed by descriptive qualitative. The results of researchin the category ofveryhigh(96,57). Pedagogicalcompetence include: 1) Have an understanding of insight or educational foundation (93.33%), 2) Having anunderstanding of the students (98.33%), 3) Able to develop curriculum / syllabus (93.33%), 4) able to draft thestudy (92.22%), 5) Implement educational and dialogical learning (90.83%), 6) to evaluate learning outcomeswith the correct procedure (87.62%), and 7) able to develop the potential of learners to mengaktulisasikanpotentials (85%).